Could a national wage rule stabilize the current account and functional income distribution in the Euro area? A study on wages, profits, and prices in peripheral countries - Camille Logeay; Heike Joebges (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
Since the introduction of the euro, divergent nominal wage developments in member countries contributed to economic imbalances, prominently visible in the current account. Wages are factor costs and as such key determinants of the price competitiveness of the tradable sector and the domestic price level of the whole economy in a monetary union. As income, they are an important determinant of domestic demand and imports. Building on the work of Horn/Logeay (2004), Herr/Horn (2012), and Onaran/Stockhammer (2016), this paper discusses how the adoption of a wage rule in member countries can help address the problem of economic imbalances. Yet, in contrast to the debate about wage-led vs. profit-led countries, and the overall growth effect of wage developments, we focus on the relationship between wages and the current account as well as the one between wages, prices, and functional income distribution. While we recommend the wage rule for all member countries, this article focuses on selected crisis countries. We first assess two conditions which are necessary in order for the wage rule to be valid: 1) demand aspects (the increase in domestic demand resulting from increased wages) outweigh cost aspects (the decrease in price competitiveness resulting from higher wages), 2) distributional effects do not prevent the transmission from wages to prices. We conclude that the implementation of the wage rule in member countries would have dampened economic divergences in the euro area, including current account imbalances. To promote the inclusion of the wage rule in all member countries, we recommend including the wage rule as a relevant indicator for the MIP-scoreboard of the European Commission, alongside support for labour market institutions. Furthermore, in order to stabilize the functional income distribution, profits (and taxes) would have to follow a similar rule.
Keywords: E25; E65; F45; 330